Competitive water polo. Upper extremity injuries - Colville, J. M.; Markman, B. S. (Clinics in Sports Medicine, 1999)
Water polo is a contact sport combining the skills of swimming, swim conditioning, throwing and, occasionally, the elements of wrestling and boxing. As such, the athletes frequently sustain upper extremity injuries involving the shoulder, the elbow, or the hand and fingers; moreover, injuries may result from either overuse or acute trauma. Successful treatment of these injuries requires an understanding of the peculiarities of the game and the likely mechanisms of injury, and the experience to properly recognize when they occur.